Marksistlikust ateismist massilise ebausuni. Mõningaid tähelepanekuid rahvapärase ateismi kohta XXI sajandi alguse Eestis - Remmel, Atko (Usuteaduslik Ajakiri, 2013)
From Marxist Atheism to Mass Superstition. Some Observations About Popular Atheism in Estonia at the Beginning of the 21th Century The article deals with the beliefs of Estonian atheists 20 years after the collapse of the atheistic Soviet Union. The situation is somewhat complex: besides religious-critical national narrative there are three atheistic traditions present in the recent Estonian history – Soviet vulgar atheism, Soviet “scientific atheism” and “new atheism”, which originates mainly from the religious scene of the United States. This raises the question: what are the standing points of Estonian atheists and which of the aforementioned traditions is the most influential? The study is divided into two parts: the first part uses the qualitative method to analyse atheistic internet comments of articles about religion in Estonian newspapers; the latter uses the quantitative method on data of sociological survey “Of Life, Religion and Religious Life”, conducted in 2010 (EUU 2010). Unlike commentaries which show passionate and intolerant struggle against any expression of religion, the sociological survey reveals Estonians’ absolute lack of interest in religion and that includes atheists as well. Therefore, Estonian atheists’ attitude towards religion can be described as tolerance based on total indifference. Due to the discussed developments Estonian popular atheism does not differ much from average Estonian’s beliefs and can be described as “practical” (no connection with religious institutions) or even “spiritual atheism”. The last description brings to notice the fact that individuals’ self-image does not say much about their actual beliefs and the borderline between belief and unbelief is not explicit, but “porous”.